Metal‐free fast azidation by using tetrabutylammonium azide : effective synthesis of alkyl azides and well‐defined azido‐end polymethacrylates - Wang, Chen-Gang (2020)
An effective method to synthesize azido‐end polymethacrylates from tetrabutylammonium azide (BNN3) in a nonpolar solvent (toluene) was developed. Several low‐mass alkyl halides were reacted with BNN3 in toluene as model reactions and the rate constants of these reactions were determined, to confirm fast BNN3 azidation for tertiary and secondary halides. The end‐group transformation of halide‐end polymethacrylates was effective and nearly quantitative. Notably, the combination of organocatalyzed living (or reversible deactivation) radical polymerization and BNN3 azidation enabled the metal‐free synthesis of azido‐end polymethacrylates, including single‐azido‐end and multi‐azido‐end functional homopolymers and block copolymers. The rapid and quantitative reaction without the requirement for a large excess of BNN3, metal‐free and polar‐solvent‐free nature, and broad polymer scope are attractive features of this azidation.